The LISA Pathfinder mission - Antonucci, F; Armano, M; Audley, H; Auger, G; Benedetti, M; Binetruy, P; Bogenstahl, J; Bortoluzzi, D; Bosetti, P; Brandt, N; Caleno, M; Cañizares, P; et al. (2012)
In this paper, we describe the current status of the LISA Pathfinder mission, a precursor mission aimed at demonstrating key technologies for future space-based gravitational wave detectors, like LISA. Since much of the flight hardware has already been constructed and tested, we will show that performance measurements and analysis of these flight components lead to an expected performance of the LISA Pathfinder which is a significant improvement over the mission requirements, and which actually reaches the LISA requirements over the entire LISA Pathfinder measurement band. © 2012 IOP Publishing Ltd.